Uji Sensitivitas Air Perasan Daun Sirih Merah (Piper crocatum) terhadap Pertumbuhan Bakteri Shigella dysentriae - SIPAYUNG, LEO PARDON; NASUTION, ILHAM SYAHRIL (Journal of Engineering and Information Technology for Community Service, 2024)
Sensitivity Test of Red Betel Leaf Pressed Water Against the Growth of Shigelladysenteriae Bacteria. The purpose of this study was to determine whether red betel leaf juice can inhibit or kill the growth of Shigella dysenteriae bacteria. Ujidaya antibacterial inhibition by using the Kirby bauerd agar diffusion method is characterized by the diameter of the inhibition zone on the media and calculated using a ruler in millimeters. The research was conducted in April 2024 at the Dr. Rusdi Health Polytechnic Laboratory. Samples in the form of red betel leaf juice made in several concentrations, namely 5%, 10%, 20%, 30%, 40%, 50%, 60%, 70%, 80%, 90%, and 100%. Made on two different media, namely Mueller Hinton Agar media and Nutrient Agar media. The results showed that all concentrations of red betel leaf juice in two different media could not kill Shigella dysenteriae bacteria, this was evidenced by the absence of a clear zone around the disc paper with a diameter of 19 mm.